2019
DOI: 10.1016/j.fuel.2018.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Entropy scaling based viscosity predictions for hydrocarbon mixtures and diesel fuels up to extreme conditions

Abstract: An entropy scaling based technique using the Perturbed-Chain Statistical Associating Fluid Theory is described for predicting the viscosity of hydrocarbon mixtures and diesel fuels up to high temperatures and high pressures. The compounds found in diesel fuels or hydrocarbon mixtures are represented as a single pseudo-component. The model is not fit to viscosity data but is predictive up to high temperatures and pressures with input of only two calculated or measured mixture properties: the number averaged mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 80 publications
0
40
0
Order By: Relevance
“…This observation was developed into a calculation methodology by Novak 76,77 and further generalized by Lötgering-Lin and Gross 46 who use the PC-SAFT EoS 22 with a GC method for calculating the viscosity correlation coefficients needed to predict viscosity. Here we provide a brief overview of Rokni et al's technique and direct the reader to the SI and elsewhere 45 for additional details. In this instance,…”
Section: Pseudo-component Model For Viscositymentioning
confidence: 99%
See 2 more Smart Citations
“…This observation was developed into a calculation methodology by Novak 76,77 and further generalized by Lötgering-Lin and Gross 46 who use the PC-SAFT EoS 22 with a GC method for calculating the viscosity correlation coefficients needed to predict viscosity. Here we provide a brief overview of Rokni et al's technique and direct the reader to the SI and elsewhere 45 for additional details. In this instance,…”
Section: Pseudo-component Model For Viscositymentioning
confidence: 99%
“…There are also several methods for modeling the viscosity of complex mixtures, including expanded fluid theory [31][32][33][34] , friction theory [35][36][37][38][39] , free volume theory (FVT) 40,41 , hard sphere models [42][43][44] , residual entropy scaling 45,46 , Eyring's absolute rate theory 47,48 , and GC methods [49][50][51][52] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pure compound PC-SAFT parameters are determined by directly fitting to properties (e.g., saturated liquid density and vapor pressure data) or using group contribution (GC) methods [49][50][51]. In this study, the PC-SAFT parameters are determined using the GC parameters of Sauer et al [49] to be consistent with our earlier reported technique to predict viscosity [52]. However, in general, other PC-SAFT GC parameters could be used, such as those reported by Tihic et al [53] or Burgess et al [54].…”
Section: Pc-saft Pseudo-component Techniquementioning
confidence: 83%
“…Figure 1 shows these coefficients plotted versus MW for n-alkanes and PNAs, and the correlations are listed in Table 3. In our previous study [52]…”
Section: Pc-saft Pseudo-component Techniquementioning
confidence: 89%